Genetic variation in the beta-2 adrenergic receptor is associated with chronic musculoskeletal complaints in adolescents - Skouen, J.; Smith, Anne; Warrington, N.; O'Sullivan, Peter; McKenzie, Luke; Pennell, C.; Straker, Leon (John Wiley & Sons Ltd., 2012)
Background: There is significant evidence to suggest that psychological and stress-related factors are important predictors of the onset of chronic widespread pain (CWP) and fibromyalgia (FM). The hypothalamic-pituitary-adrenal axis, together with the efferent sympathetic/adrenomedullary system, influence all body organs (including muscles) during short- and long-term threatening stimuli. The aim of this study was to investigate the relationship between genetic variants in adrenergic candidate genes and chronic musculoskeletal complaints (MSCs) in adolescents. Methods: Adolescents from the Western Australian Pregnancy (Raine) Cohort attending the 17-year cohort review completed a questionnaire containing a broad range of psychosocial factors and pain assessment (n = 1004). Blood samples were collected for DNA extraction and genotyping. Genotype data was obtained for 14 single nucleotide polymorphisms (SNPs) in two candidate genes – beta-2 adrenergic receptor (ADRB2) and catecholamine-O-methyltransferase (COMT). Haplotypes were reconstructed for all individuals with genotype data. Results and Conclusion: Both female gender and poor mental health were associated with (1) an increased risk for chronic, disabling comorbid neck and low back pain (CDCP); and (2) an increase in the number of areas of pain. Of the 14 SNPs evaluated, only SNP rs2053044 (ADRB2, recessive model) displayed an association with CDCP [odds ratio (OR) = 2.49; 95% confidence interval (CI) = 1.25, 4.98; p = 0.01] and pain in three to four pain areas in the last month (OR = 1.86; 95% CI = 1.13, 3.06; p = 0.02). These data suggest that genetic variants in ADRB2 may be involved in chronic MSCs.